Early Acute Kidney Injury: Examine the Prevalence, Risk Factors and Outcomes in Non-Surgical Patients (Medical Forum Monthly, 2024)
Objective: To examine the prevalence of early acute kidney injury, risk factors and outcomes of life threatening disorder.Study Design: Retrospective/Observational study.Place and Duration of Study: This study was conducted at the Department of Nephrology, Shaikh Zayed Hospital Lahore from October 2018 to March 2019.Materials and Methods: Total 200 patients of both genders with ages above 20 years were included. Patients demographic such as age, sex, residence were recorded after taking informed consent. Incidence of early acute kidney injury was examined during first 5 days of hospitalization. Acute kidney injury patients were screened according to Kidney Disease Improved Global Outcomes (KDIGO) guidelines. Risk factors associated to acute kidney injury were analyzed. Outcome in term of mortality was examined.Results: There were 120 (60%) male patients and 80 (40%) were females with mean age 38.15+12.45 years. Forty (20%) patients were diagnosed to had acute kidney injury in which majority of patients 30 (75%) patients were male. Twelve (30%) patients had AKI stage I, 15 (37.5%) patients had stage II and 13 (32.5%) had AKI stage III. Pre-hospital nephrotoxic use, delay hospitalization, sepsis, age and low education were the associated risk factors of AKI (p=<0.05). Ten (5%) patients died in which 9 had AKI.Conclusion: Prevalence of early acute kidney injury is high in hospitalized patients. Nephrotoxic use, sepsis, delay hospitalization and older age were the associated risk factors. Mortality rate is also high in patients with acute kidney injury.